2022
DOI: 10.1111/jcpp.13625
|View full text |Cite
|
Sign up to set email alerts
|

Positive maternal mental health during pregnancy and mental and behavioral disorders in children: A prospective pregnancy cohort study

Abstract: Background: The role of positive maternal mental health during pregnancy in child mental health remains largely unknown. We investigated whether positive maternal mental health during pregnancy is associated with lower hazards of mental and behavioral disorders in children and mitigates the adverse effects of negative maternal mental health. Methods: Among 3,378 mother-child dyads of the Prediction and Prevention of Preeclampsia and Intrauterine Growth Restriction study, mothers reported their positive mental … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
11
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 33 publications
4
11
0
1
Order By: Relevance
“…In conclusion, based on the findings of Lähdepuro et al. (2023) we recommend that research should study both biological and psychological mechanisms underlying the association between positive maternal mental health during pregnancy and child outcomes and invest in the development, optimization, and evaluation of positive mental health increasing interventions during pregnancy, especially for pregnant women with mental health problems. Investing in the promotion of positive maternal mental health during pregnancy concerns a promising public health approach and has the potential to improve maternal perinatal mental health and behavioral and developmental outcomes of future generations.…”
Section: Investing In Interventions Promoting Positive Mental Health ...mentioning
confidence: 93%
See 3 more Smart Citations
“…In conclusion, based on the findings of Lähdepuro et al. (2023) we recommend that research should study both biological and psychological mechanisms underlying the association between positive maternal mental health during pregnancy and child outcomes and invest in the development, optimization, and evaluation of positive mental health increasing interventions during pregnancy, especially for pregnant women with mental health problems. Investing in the promotion of positive maternal mental health during pregnancy concerns a promising public health approach and has the potential to improve maternal perinatal mental health and behavioral and developmental outcomes of future generations.…”
Section: Investing In Interventions Promoting Positive Mental Health ...mentioning
confidence: 93%
“…Interestingly, positive maternal mental health during pregnancy positively influences the maternal stress response and reduces the risk of developing mental health problems during pregnancy (Kumar et al., 2022; Lähdepuro et al., 2023). Positive mental health may thus represent a source of resilience protecting against the long‐term negative effects of prenatal exposure to maternal mental health problems on the offspring.…”
Section: Resilience Mechanisms During Pregnancymentioning
confidence: 99%
See 2 more Smart Citations
“…For child development in the other hand, parental psychological well-being is associated with health behavior [12] and parenting behavior [13], which may impact child development [14]. For example, prenatal 4 maternal positive mental health was associated with a lower risk of mental illness in children [15] and reduced the effect of maternal stress on children internalizing and externalizing symptoms [16]. In addition, a longitudinal study reported that positive maternal perinatal mental health is associated with more favorable developmental outcomes in toddlers, particularly regarding cognition, communication, and social development [17].…”
Section: Introductionmentioning
confidence: 99%